Optimization of zirconia nanopowder precipitation process using Taguchi experimental design methodology - Yasaman Jalinousi; Ali Yadollahi; Kamal Saberyan (Scientific Reports)
Abstract The purpose of this research is to investigate the production of ZrO2 nano-powder from the product of the alkaline fusion process of Zircon mineral. The effect of surfactant type, solution pH, and calcination temperature were investigating using L9 orthogonal array in the Taguchi design of experiment method. The experiments related to the Preparation of Zirconia nano-powder were first performed on a synthetic solution prepared by dissolving Zirconium tetrachloride in deionized water. The final tests were performed on the solution obtained from the acidic leaching step in the alkali decomposition of the Zircon mineral. According to the results, the optimal conditions for ZrO2 nano-powder production from synthetic solution involved pH = 7, PVP as a surfactant, and 300 °C calcination temperature, resulting in 10.5 nm ZrO2. Applying these optimal conditions on the real Zirconium solution from the alkaline fusion process of Zircon resulted in the Preparation of 26.6 nm ZrO2 nano-powders